Composite nanofibers through in-situ reduction with abundant active sites as flexible and stable anode for lithium ion batteries. (15th March 2019) - Wu, Songhao; Han, Yidong; Wen, Kechun; Wei, Zhaohuan; Chen, Dongjiang; Lv, Weiqiang; Lei, Tianyu; Xiong, Jie; Gu, Meng; He, Weidong
Abstract: Due to the flexibility and excellent electrochemical properties, carbon nanofibers have been proposed as promising anode material for lithium ion batteries. In this paper, through in-situ reduction of C/CuO/rGO after electrospinning to form abundant active sites at carbon nanofibers, a novel C/Cu/rGO anode is prepared. The C/Cu/rGO anode owns a capacity of ∼400 mAh/g at 1 A/g after 600 cycles, a value well above those of C and C/rGO (<200 mAh/g). Cu nanoparticles greatly improve the lithium storage performance by forming defects as active sites for ion storage and owning a pseudo capacitance due the interrupted ordered atomic arrangement and the increase of surface desaturation in the anode. Synergistically, rGO improves the conductivity and stability. This work provides an efficient anode materials platform towards high-capacity and flexible lithium ion batteries. Graphical abstract: A flexible, stable, high-performance anode for the lithium-Ion battery is obtained through in-situ reduction of C/CuO/rGO with electrospinning technology. The anode delivers a specific capacitance of ∼400 mAh/g at 1 A/g after 600 cycles, a value well above those of C and C/rGO (<200 mAh/g).Image 1